Aplikasi Peminjaman Buku Pada Perpustakaan Menggunakan Kartu Tanda Siswa (KTS) - Ismail, Muh; Zainal, Muhammad; Multi Lahan, Sumantri (Jurnal Sintaks Logika, 2021)
Data processing and information dissemination in school libraries often encounter obstacles or problems, if the source is still in the form of static paper or relies on someone's memory as a storage medium, causing various problems such as data loss. Through the library automation system, the library management process is expected to run more effectively and efficiently. So the development of a library that uses an RFID system for library managers can help library managers so that they can store book data in the library using the system. And can also find out what books are being lent and have not been returned by using a database that contains data on a collection of books and members. In this study, the author produces a system using a Delphi desktop application integrated with RFID and Barcode so that the stored data is more secure because it is an application where the data is stored safely.